ANALISIS KUALITAS FASILITAS TERHADAP KEPUASAN PENGUNJUNG DI TAMAN TENGKU SYARIFAH AMINAH SIAK - Ginda Rajin; Zahara Fatimah; Supardi; Andri Wibowo (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
Urban parks as public tourism spaces play an important role in supporting recreational activities and enhancing regional tourism attractiveness. However, the quality and facilities provided do not always optimally generate visitor satisfaction. This study aims to analyze the effect of quality and facilities of public tourism spaces on visitor satisfaction at Tengku Syarifah Aminah Park, Siak. A quantitative approach was employed using a survey method, with data collected from 100 visitors through questionnaires and analyzed using multiple linear regression. The results indicate that quality and facilities have a positive and significant effect on visitor satisfaction, both partially and simultaneously. These findings suggest that improving the quality of management and facilities of public tourism spaces directly contributes to better visitor experiences. This study provides practical implications for park managers and local governments in developing visitor-oriented public tourism space management strategies.